Proceedings of the 2016 Global Conference on Business, Management and Entrepreneurship 2016
DOI: 10.2991/gcbme-16.2016.28
|View full text |Cite
|
Sign up to set email alerts
|

Sharia Compliance on Murabaha Financing

Abstract: This research aims to find out how the sharia compliance supervision on murabaha financing, as well as things become supporters and obstacles in fulfillment of sharia principles on murabaha financing at BMT. This study used a qualitative descriptive method. The data used is Primary data were obtained from interviews. Determination of data sources using purposive sampling method by interviewing people who were directly involved in the practice as well as the supervision of murabaha financing. Mechanical testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Research on BMT Yogyakarta found that BMT in general has implemented internal control, but there are still weaknesses in the authorization procedures. From 19 samples, only 11 BMT has SSB [17].…”
Section: Standardization Of Shari'ah Supervisory Board Authors Andmentioning
confidence: 99%
“…Research on BMT Yogyakarta found that BMT in general has implemented internal control, but there are still weaknesses in the authorization procedures. From 19 samples, only 11 BMT has SSB [17].…”
Section: Standardization Of Shari'ah Supervisory Board Authors Andmentioning
confidence: 99%
“…A leverage ratio is a tool for assessing a company's leverage. Overuse of debt puts businesses at risk as they fall into the extreme debt category, which means that businesses will end up in high debt, and the debt burden will be difficult to resolve (Mediawati, 2016). Liquidity Ratio is the ratio used to interpret short-term financial position.…”
Section: Introductionmentioning
confidence: 99%
“…BMT is a business organization that also play a social function and role of the BMT as follows: As an investment manager, to play its role as an agent or as a liaison for the owners of the funds; As an investor, if the source of the funds obtained from members or loans from other parties are then managed in professional and effective without the special requirements of the owner of the fund; Social function, providing better social services to members and dhua'fa (Mediawati and Agustami 2016).…”
Section: Introductionmentioning
confidence: 99%